URBAN COMMUNICATION RESEARCH GRANT - Christidis, Yiannis (My University, 2026)
Christidis was awarded the prize for his research project Soundscapes, Communities and Place Attachment in Urban Space: a study on the soundmarks of divided Nicosia and their effects.
Keywords: Social sciences